Arah Kebijakan Badan Usaha Milik Negara - Achmad Zahruddin (SOSIALITA, 2016)
This time there are still many corporate governments are still not managed well, because workers are not professional so uncompetitive, their pragmentation manager because of a bureaucratic culture that is still dominant, and politicized existence, consequently in society appears streotip that the management of corporate government  happen trends slow and inefficient , so that the urgent problem is to create a professional management. For that departs from the same vision that the key to successful  corporate government depends on the quality of labor followed by a reference work within the framework of Good Corporate Governance.However Restructuring is not the final word for the direction of policy preparation good corporate government. Restructuring seek only the initial basis for the next step, namely the professionalism of enterprises, both in terms of its owner (no excessive interference anymore  of the  owners represented by its technical department) as well as professional actors in the Corporate government. This step will be more strategic than in thinking  how to make  soon go public of corporate  or privatized, however, to change the direction of the organization's management that the bureaucracy towards the management policy of corporate organization, the entire State Owned Enterprises should implement the Good Corporate Gavernance. (GCG).